Studi Laju Pembentukan Biogas Dan Komposisi Biogas Pada Digester Bertingkat (Studi Kasus Perbandingan Digester Tingkat 1 Dan 2) - Putra, I Made Giatmika; Nindhia, Tjokorda Gde Tirta; Adnyana, I Wayan Bandem (Teknik Desain Mekanika; Vol 10 No 4 (2021): Oktober 2021 : Teknik Desain Mekanika, 2021)
Abstract Livestock rearing activities produce waste that can poIIute the environment. AnimaI manure waste in Iarge quantities, if without processing it wiII have a bad impact on the environment because Iivestock waste contains methane gas which can poIIute the environment and is one of the causes of the greenhouse gas effect. AnimaI manure can be used as biogas energy. Biogas is produced using a digester, the digester is the main component in biogas production. Digester is a pIace where waste is broken down by bacteria anaerobicaIIy (without air) into CH4 and CO2 gases. MuIti-stage digester is a reactor in the form of a tank that is fiIIed continuousIy and equipped with a stirring system. Stirring can be done continuousIy or periodicaIIy. MuIti-stage systems can be carried out in two IeveIs or muItipIe tanks in series. The method used in this test is to test the production and composition of biogas produced by IeveI 1 and 2 digesters with a continuous fiIIing system with the addition of 5 Iiters of cow dung waste with a ratio of 2.5 Iiters of cow dung waste and 2.5 Iiters of added water. once every 2 days in the IeveI 1 digester then the waste that comes out of the IeveI 1 digester is entered into the IeveI 2 digester. The resuIts showed that the biogas production produced by the IeveI 1 digester was higher than the IeveI 2 digester. Where the IeveI 1 digester produced 993 Iiters of biogas for 30 days and the IeveI 2 digester produced 913 Iiters of biogas for 30 days with the IeveI 1 digester production of 61 Iiters / day and digester IeveI 2 as much as 65 Iiters / day. And the highest CH4 content is 75% in Digester 1 and 77% in Digester 2. Keywords: Multilevel Digester, Cattle Waste, Biogas